Green leadership for a sustainable future: The path from innovation to enhanced project performance - Altaf, Saqib; Wenyuan, Li; Altaf, Nasira; Siddiqui, Muhammad Kamran; Shahbaz, Muhammad (International Journal of Emerging Trends in Social Sciences, 2025)
The effectiveness of green initiatives has emerged as a crucial goal for entities seeking to balance economic growth with environmental responsibility. This study examines how green horizontal leadership impacts the performance of green projects, emphasizing the mediating roles of green proactive innovation and green reactive innovation. This study investigates the role of leadership in fostering innovation and enhancing sustainability outcomes through the application of stewardship theory, organizational learning theory, and the resource-based view (RBV). A quantitative survey was conducted among enterprises in Jiangsu Province, China, a region noted for its industrial and economic development alongside its increasing environmental initiatives. Leadership, innovation, and project performance were examined using structural equation modeling. Green horizontal leadership promotes green project performance by mediating proactive and reactive innovation. Participatory and decentralized leadership styles improve environmental outcomes through strategic and compliance-focused sustainability programs. Merging multiple views, the study provides theoretical insights into leadership and environmental sustainability success. Organizations seeking sustainability through leadership development, investment in green innovations, and flexible laws have demonstrable results. Future research will expand the study's geographic coverage and examine other mediating factors that affect leadership, innovation, and performance.